การอพยพของชาวยูนนานเข้าสู่เวียดนามตั้งแต่สมัยโบราณถึงคริสต์ศตวรรษที่ 19 /Migration of Yunnan people into Vietnam during ancient time to 19th century - Liu, XuYin; เมตตาริกานนท์, ดารารัตน์; นาราสัจจ์, เบญจวรรณ (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
Yunnan is located in the Southwest of China, bordered by Vietnam. So, Yunnan and Vietnam have close relationship. Also, Yunnan people have continuously migrated to Vietnam since ancient time. This article aimed to study the migration of Yunnan people into Vietnam during ancient time to 19th century. The historical research method was employed. The data were mainly analyzed from Chinese documents. The study indicated that the migration of Yunnan people into Vietnam was divided into two periods. (1) From ancient time to the year 938: It was the time when Vietnam was under Chinese rule, and the Nanzhao Kingdom was located in the Yunnan area. Some Yunnan people migrated to Vietnam for trading, war and political reasons by using three land and water routes. The first route was from Miling (Vietnam) to Yizhou (Yunnan). The second route connected between Erhai Lake (Yunnan) and Vietnam. The third route started from Annan (Vietnam) to Dali (Yunnan). (2) During 939-1885: Vietnam was independent from China. Traditional land and water routes connecting between Yunnan and Vietnam (third route) were developed. Two land and water routes were also opened, starting from Mengzi (Yunnan). The first route was to the Fuliang River (Vietnam), and the second route was to Bahesanqijiang which was the junction of the Red River, the Lo River and the Black River. During this time, the number of Yunnan people immigrated to Vietnam was continuously increasing. The causes of migration were more diverse, including the reasons of economy, trading, mining, politics, war, being forcibly moved by Vietnam, escaping from the arrest of the government, the impact of the abolition of “Tusi” system and the evasion of the rebellion suppression.